Perancangan Sistem Pakar Diagnosa Penyakit Jantung Berbasis Web Menggunakan Metode Fuzzy Mamdani (Studi Kasus : Dinas Kesehatan Rangkasbitung) - Putri Nuraeni, Desiana (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The heart is one of the most important organs of the human body and plays a vital role in human life. The main function of the heart is to pump blood into the lungs where it will be saturated with oxygen (O2), and then pump it out into the body to supply cells with oxygen (O2). However, the heart has a huge risk of disease and can be very fatal. Various causes can affect human heart health, especially unhealthy lifestyles and diets. Heart disease is a disease that causes a high mortality rate in Indonesia based on research conducted by the World Health Organization (WHO, 2014). Therefore, anticipation of the risk of heart disease is very necessary. This research designs a disease diagnosis website. The results of this study can provide an overview and explanation to users in diagnosing early heart disease based on symptoms or causes that exist quickly and precisely.  In addition, this application makes it easier for users to provide an overview of the health information of heart disease experienced and provide knowledge about the types of heart disease and symptoms, causes along with actions that must be taken for prevention as an initial step in anticipating heart disease.